UPAYA PENINGKATAN PRODUKTIFITAS PEMBUATAN SANGKAR BURUNG BERBASIS ROTAN KETIKA MUSIM HUJAN - Nugroho, Arif Setyo; Rahayu, Aris Teguh; NS, Muhammad Nur Cahyo; N, Rohmat Aditya Dwi (Fakultas Teknik dan Ilmu Komputer (FASTIKOM) UNSIQ, 2024)
A group of young people from Jegrik village, Karanganyar district, have a business making bird cages. The shape of bird cages they make are oval-shaped bird cages, which are used to cage turtle doves, puter birds, and turtle doves. Making bird cages using rattan as raw material. With the technology developed in the form of a blengker mal tool that utilizes the heat propagation of fire, this tool is a solution to the problems that occur during the rainy season, where heat from the sun is needed to make the blengker, but often there is no sunlight, which hampers production. It's different when during the dry season the heat of the sun is used to make blengker. Problems during the rainy season can be overcome with heating devices that utilize a heat propagation system from a flame that spreads its heat to the walls of the device. The heat comes from the flame from the LPG gas stove. To make a blengker, it only takes approximately 7 minutes, the heat on the walls of the blender is approximately 40oC-70oC.